Predictive Factors of Diabetes Distress Among Indonesian Older Persons With Type 2 Diabetes Mellitus - Muhammad Ischaq Nabil Asshiddiqi (Prince of Songkla University, 2022)
Thesis (M.N.S. (Adult and Gerontological Nursing)--Prince of Songkla University, 2019